The Effect of Variation of Raw Materials and Addition of Molasses Adhesive on the Quality of Blotong Bricket - Caecilia Pujiastuti; Okta Maulidian; Putri Nur Wahyuni; AR Yelvia Sunarti (Future Science, 2022)
Blotong is one of the wastes produced by sugar factories that have the potential to be used as an alternative fuel. The cellulose content contained in blotong has the potential to be used as raw material for making briquettes. This study aims to determine the effect of the composition of blotong and banana midrib with molasses adhesive on the moisture content and ash content of the resulting briquettes. The manufacture of briquettes is carried out by several procedures, such as the preparation of raw materials starting from drying and size reduction, then cured using a pyrolyzer, refining and sifting, printing, and drying briquettes. The results showed that the addition of banana fronds and molasses adhesive could increase the water content and reduce the ash content of blotong briquettes. The results showed that the addition of banana fronds and molasses adhesive could increase the water content and reduce the ash content of blotong briquettes. The lowest ash content was found in the ratio of blotong: banana midrib (50: 50) which was 32.0489%. The best water content is found in the ratio of blotong: banana midrib (70: 30). The results showed that the addition of banana fronds and molasses adhesive could increase the water content and reduce the ash content of blotong briquettes.